A case of disseminated histoplasmosis diagnosed after oral presentation in an old HIV‐negative patient in Sweden. (10th September 2014) - Mota de Almeida, Fernando J.; Kivijärvi, Kristina; Roos, Göran; Nylander, Karin
<x xml:space="preserve">Abstract</x> Histoplasmosis is an endemic disease in various regions such as North America and South‐East Asia but remains rare in Europe. Disseminated histoplasmosis is unusual in HIV‐negative patients. Here, we describe a case of disseminated histoplasmosis in an HIV‐negative patient diagnosed after oral presentation.